Representações docentes sobre o currículo integrado em saúde - Silva, Elaine do Nascimento (2016)
During professional activities developed in discussion areas over the curricular changes within a college institution, it has come to attention that an intervention in the education process involves, besides policies and structural adaptations, the commitment of all the subjects involved, under the penalty of not reaching the expected goals and the inadequacy of what envisages the national curricular guidelines which pointed towards a wider health conception and established, as the desired goal for the course organization, the integrated curriculums. With the objective of identifying faculty representations about integrated curriculum in health, this field study, descriptive of a qualitative approach, using open or in depth interview with eleven lecturers of a State University, as an instrument of production of data, being the same analyzed by means of the technique of Content Analysis. The data indicate that the theoretical knowledge about integrated curriculum among respondents is still incipient, requiring further development. Teachers recognize that do not have the educational preparation necessary to exercise integrative teaching practice, with the understanding that it is a matter of urgency the need for the institution to assume its role in continuing education to act in this new proposal, going beyond the epistemological discussions and deepen the discussions on the implementation of these new curricula, seeking for new strategies for greater faculty involvement, since there is a strong resistance for change. Thus, in order to offer a research response to the study subjects and the institution, it was proposed as the product of the intervention the "Integrated Curriculum Forum: challenges and opportunities for implementation, with the objective of enabling the teacher to act in front of the new educational policy of the institution.